Faith and the Family: Family Life and the Spread of Evangelical Culture in the Scottish Gàidhealtachd, c. 1790–c. 1860. (April 2021) - Ritchie, Elizabeth
Abstract : This examination of the Scottish Gàidhealtachd (Gaelic-speaking area) extends beyond protestant ideas about the gendered family to how people actually implemented spiritual practices at home. The results complicate earlier conclusions, showing that family worship undermined as well as reinforced the patriarchal family. The challenge to fathers' authority came less from the influence of mothers than from children and non-family members who, through literacy, became better equipped than fathers for spiritual leadership. Examining family life shows how some Gaels used evangelicalism to reshape their culture while also exposing how others resisted this change.